Belen Salvatierra and the Psychology in Arequipa - Arias Gallegos, Walter L. (2020)
In this work, historical sort of, we review and analyze the life and work of Belen Salvatierra, one of the most relevant psychologist in our country. Her family, professional studies and her academic production are the target of this research, so there are not dado previous papers about her contributions given to the Peruvian psychology. We review her books, conferences and research articles; so as her management work as Dean of the Faculty of Psychology and Industrial Relations, which strength the process of professionalization of psychology in Arequipa. Moreover, we review her research in the lines of family studies, neuropsychology and occupational health.